Smc5–Smc6 mediate DNA double-strand-break repair by promoting sister-chromatid recombination - De Piccoli, Giacomo (Nat Cell Biol, 2006)
DNA double-strand breaks (DSB) can arise during DNA replication, or after exposure to DNA-damaging agents, and their correct repair is fundamental for cell survival and genomic stability. Here, we show that the Smc5–Smc6 complex is recruited to DSBs de novo to support their repair by homologous recombination between sister chromatids. In addition, we demonstrate that Smc5–Smc6 is necessary to suppress gross chromosomal rearrangements. Our findings show that the Smc5–Smc6 complex is essential for genome stability as it promotes repair of DSBs by error-free sister-chromatid recombination (SCR), thereby suppressing inappropriate non-sister recombination events.